A comprehensive study of enhanced characteristics with localized transition in interface-type vanadium-based devices. (June 2020) - Lin, C.-Y.; Chen, P.-H.; Chang, T.-C.; Huang, W.-C.; Tan, Y.-F.; Lin, Y.-H.; Chen, W.-C.; Lin, C.-C.; Chang, Y.-F.; Chen, Y.-C.; Huang, H.-C.; Ma, X.-H.; et al.
Abstract: In this research, we investigated the conduction mechanism in metal-insulator transition (MIT) materials. Among these MIT materials (NbOx, NiOx, VOx, and TaS2 ), vanadium oxide–based selectors have been widely investigated because of their high switching speed ( 10-ns transition time), sufficient non-linearity (>10 3 ), and endurance stability ( 10 10 ). Abnormal temperature-dependent degradation in the high resistive state was observed, as was studied in detail by a current fitting analysis and explored theoretically by electric (E-MIT) and thermal (T-MIT) modeling. The results suggest the existence of a MIT region located between the electrode and the localized filament. To improve the localized transition efficiency, we propose an enhanced-type MIT architecture to bypass the E-MIT and T-MIT universal rule with the novel structure of vanadium top electrode device. As compared with a vanadium oxide middle-layer device, the electrical transition efficiency is improved 2-fold as evidenced by thermal cycling material analysis, as well as boosting endurance reliability to 10 7 at 65 °C. Finally, for the first time, a potential neuromorphic computing application featuring a damping oscillator has been demonstrated in this enhanced-type MIT architecture, with a high damping ratio with 10-fold smaller area and 5-fold smaller energy than complementary metal–oxide–semiconductor (CMOS) devices. This presents a promising milestone for ultralow power neuromorphic system design and solutions in the near future. Graphical abstract: Image 1 Highlights: Complete electrical, material analysis and simulation are performed to analysis the proposed universal model. Threshold characteristics are observed and formed by applying vanadium as the electrode. The proposed models are proven by transmission electron microscopy images of the vanadium oxide in the vanadium electrode. An example of damping oscillation is demonstrated with only one selector connected to one external resistor. The physical model was constructed to explain current conduction of metal-insulator transition mechanism.